2000
DOI: 10.1099/00221287-146-3-639
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of the secretin OutD suppresses the secretion defect of an Erwinia chrysanthemi outB mutant

Abstract: OutB is a component of the Erwinia chrysanthemi Out secretion machinery. Homologues of OutB have been described in two other bacteria, Klebsiella oxytoca and Aeromonas hydrophila, but their requirement in the secretion process seems to be different. Study of OutB topology with the BlaM topology probe suggests that it is an inner-membrane protein with a large periplasmic domain. However, fractionation experiments indicate that it could be associated with the outer membrane through its C-terminal part. The secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…Recently, it was shown that two other Gsp proteins (probably) interact with the GspD secretin, i.e., XpsN (GspN) of Xanthomonas campestris (40) and OutB (GspB) of E. chrysanthemi (9). Genes encoding GspN have been identified in the gsp gene clusters of most GSP-containing bacteria, except E. chrysanthemi, P. aeruginosa, and P. alcaligenes (25,40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that two other Gsp proteins (probably) interact with the GspD secretin, i.e., XpsN (GspN) of Xanthomonas campestris (40) and OutB (GspB) of E. chrysanthemi (9). Genes encoding GspN have been identified in the gsp gene clusters of most GSP-containing bacteria, except E. chrysanthemi, P. aeruginosa, and P. alcaligenes (25,40).…”
Section: Discussionmentioning
confidence: 99%
“…One of the difficulties in determining whether PulS-like pilotins exist in other T2S systems is that the C-terminal regions of the secretins, to which they probably bind, are among the least conserved regions of these proteins, suggesting that the pilotins may also be poorly conserved. Other proteins, notably T2SA and T2SB (Ast et al, 2002;Condemine & Shevchik, 2000), have been proposed to perform PulS-like functions. Interestingly, E. coli K-12 has genes for T2SA and T2SB proteins within its secreton gene cluster (Francetic et al, 2000) as well as an unlinked gene, yacC, with limited similarity to pulS.…”
Section: T2s Systemsmentioning
confidence: 99%
“…One possible role of ExeB may involve a direct interaction with ExeD, as OutB and OutD can be cross-linked with formaldehyde in E. coli cells (9). To date, A. hydrophila cross-linking studies have not identified such a complex.…”
Section: Vol 187 2005mentioning
confidence: 99%
“…Although normally silent, the secreton genes of the E. coli gsp system, including gspAB, were shown to be required for secretion of chitinase (13). The importance of GspB proteins in other translocation systems, such as the pul and out systems of Klebsiella and Erwinia, has also been characterized (8,9).…”
mentioning
confidence: 99%